Preparation of mullite-TiB2-CNTs hybrid composite through spark plasma sintering. Issue 13 (September 2019) - Orooji, Yasin; Ghasali, Ehsan; Moradi, Mostafa; Derakhshandeh, Mohammad Reza; Alizadeh, Masoud; Asl, Mehdi Shahedi; Ebadzadeh, Touradj
Abstract: A near fully dense mullite-TiB2 -CNTs hybrid composite was prepared successfully trough spark plasma sintering. 1 wt%CNT and 10 wt%TiB2 were mixed with nano-sized mullite powders using a high energy mixer mill. Spark plasma sintering was carried out at 1350 °C under the primary and final pressure of 10 MPa and 30 MPa, respectively. XRD results showed mullite and TiB2 as dominant crystalline phases accompanied by tiny peaks of alumina. The microstructure of prepared composites demonstrated uniform distribution of TiB2 reinforcements in mullite matrix without any pores and porosities as a result of near fully densified spark plasma sintered composite. The fracture surface of composite revealed a proper bonding of TiB2 with mullite matrix and also areas with CNTs tunneling and superficies as a result of pulling-out phenomenon. The flexural strength of 531 ± 28 MPa, Vickers harness of 18.31 ± 0.3 GPa, and fracture toughness of 5.46 ± 0.12 MPa m −1/2 were achieved for prepared composites as the measured mechanical properties.